Evaluation of the Chagas Stat-Pak(tm) Assay for Detection of Trypanosoma cruzi Antibodies in Wildlife Reservoirs - Yabsley, Michael J. (2009)
An immunochromatographic assay (Chagas Stat-Pak™) was evaluated for the detection of Trypanosoma cruzi antibodies in 4 species of wildlife reservoirs. Antibodies to T. cruzi were detected in raccoons (Procyon lotor) (naturally and experimentally infected) and degus (Octodon degu) (experimentally-infected) using the Chagas Stat-Pak. In naturally exposed wild raccoons, the Chagas Stat-Pak had a sensitivity and specificity of 66.7–80.0% and 96.3%, respectively. Compared with indirect immunofluorescent antibody assay results, serocon-version as determined by Chagas Stat-Pak was delayed for experimentally infected raccoons, but occurred sooner in experimentally infected degus. The Chagas Stat-Pak did not detect antibodies in naturally or experimentally infected Virginia opossums (Didelphis virginiana) or in experimentally infected short-tailed opossums (Monodelphis domestica). These data suggest that the Chagas Stat-Pak might be useful in field studies of raccoons and degus when samples would not be available for more-conventional serologic assays. Because this assay did not work on either species of marsupial, the applicability of the assay should be examined before it is used in other wild species.